Civil law contract as a document - Yu. I. Chalyi (Bulletin of Kharkiv National University of Internal Affairs)
Based on the analysis of current Ukrainian legislation, practice of its application, provisions of civil law doctrine and documentary studies, it has been identified the general features of civil law contracts as documents. The need to develop theoretical provisions on a contract as a document is caused by insufficient research of these issues in the science of civil law.